Bronchiolitis in Infants; Five Years’ Experience of a Teaching Hospital - Alqahtani MH; Alqahtani MF; Asiri M; Alghamdi S; Alshagawi Z; Alzahrani S (Infection and Drug Resistance, 2023)
Mohammad Hussain Alqahtani, Mohammad Faraj Alqahtani, Mohammed Asiri, Saad Alghamdi, Ziyad Alshagawi, Saleh Alzahrani Pediatrics Department, Imam Abdulrahman Bin Faisal University King Fahd Hospital of the University, Al Khobar, Saudia ArabiaCorrespondence: Mohammad Faraj Alqahtani, Pediatrics Department, Imam Abdulrahman Bin Faisal University King Fahd Hospital of the University, Al Khobar, Saudia Arabia, Tel +966508880030, Email Ma.fq@icloud.comBackground: Bronchiolitis is a clinical syndrome affecting the lower respiratory tract of infants and toddlers < 2 years old. Variability in clinical profile and response to therapy in children with Bronchiolitis calls for studying the different clinical aspects of local patient population.Aim: The goal of our study is to determine the clinical presentation, past medical history, hospitalization course and prognosis in children below two years of age who have been hospitalized in King Fahad University Hospital over the last five years.Materials and Methods: A retrospective chart review based on electronic health records of all Bronchiolitis-related hospitalization of infants and toddlers below two years of age, covering the period between January 1, 2015, to April 26, 2020.Results: Out of a total of 446 children < 2 years of age, 202 were female (45.4%), and 243 were male (54.6%). Although the length of hospital stay was almost equal between the sexes, there was a significant (p-value=0.01) increase in length of intensive care unit stay among females compared to males. Furthermore, there was a significant prolongation in the duration of ventilator usage among females (p value = 0.062). Out of fifty-five patients admitted to the ICU, 83.63% of them were 12 months of age and below.Conclusion: Our results show a significant increase in length of ICU and ventilator use among females compared to males. It also shows that infants younger than 12 months account for most ICU admissions. These findings, among many others, may help pediatricians formulate a better diagnostic and therapeutic pathways.Keywords: bronchiolitis, respiratory syncytial virus, RSV, lower respiratory tract infection